Dispersal, settlement and recruitment : their influence on the population dynamics of intertidal mussels - Phillips, Tracey Elizabeth (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 1995)
Recruitment of planktonic larvae into sedentary benthic populations regulates the population dynamics of marine invertebrates. The processes controlling recruitment, however, are poorly understood, and recruitment remains largely unpredictable, which complicates management of exploited shellfish resources. The mussels Perna perna, Choromytilus meridionalis and Mytilus galloprovincialis, found on the south coast of southern Africa, have planktonic larvae and sedentary adult stages. This thesis examines dispersal, settlement and early post-settlement growth and mortality, and their effect on recruitment and demography of intertidal mussel populations in the region of Algoa Bay on the south coast of southern Africa. Temporal and spatial variation in the body mass, density and size structure of mussels, the distribution of bivalve larvae on plankton grids in the nearshore zone and the distribution of a recently introduced invasive mussel, Mytilus galloprovincialis, were examined between 1989 and 1992. Furthermore, data on hourly or daily changes in wind strength and direction, air and sea surface temperatures and low and high tide levels in the study region, were obtained. There were 3-4 peaks in spawning (characterised by an abrupt decline in weight) and settlement activity annually. These peaks varied in exact timing, intensity and duration between sites and over time. However, at a site, spawning was followed by settlement 4-8 weeks later, and there was a significant (P < 0.05) direct correlation between spawning intensity prior to the appearance of a new cohort and the cohort density (settlement intensity). The stochastic spatial and temporal variation in breeding activity was superimposed on a more general pattern of a higher intensity of spawning and settlement in Algoa Bay than on the open coast, and a higher settlement intensity on coastal sandstone shores than on dune rock shores. Spawning was more frequent in winter and spring, and the probability of spawning and settlement peaked around the spring and autumn equinox, if temperature and wind conditions were suitable. Larval behaviour had little effect on their dispersal in the well-mixed nearshore region. Larvae were passively dispersed by currents, and their dispersal range and direction depended on prevailing winds and local topography. The sharp decline in density of recruit and adult M. galloprovincialis with increasing distance from the point of introduction, showed that some larvae were carried by wind generated currents over moderately long distances (-100 km). However, since most (76 %) M. galloprovincialis recruited within 4 km of the parent population, it is possible that larvae become trapped in small gullies and crevices around rocky shores, and have a limited dispersal range. This could explain the link between local patterns of spawning and settlement. The distribution and abundance of settlers on the shore was influenced by larval behaviour and the availability of settlement, substrata. Larvae preferred to settle primarily on foliose coralline algae and migrate to the adult mussel bed when they were larger (0.60-7 mm), but larvae also settled directly on adult mussels, possibly because the amount of coralline algae was limited. Both direct and secondary settlement were considered to be important in maintaining mussel populations since the rate of settlement was low(generally < 60 000.m-2). Cohort analyses showed that prior to maturity post-settlement growth (- 30 mm in 10 months) and mortality rates (60-100%) were high, but varied. When settlement intensity was low this variability uncoupled the relationship between spawning and recruitment intensity. Multiple regression analysis showed that together reproductive effort (gamete output), settlement intensity, growth and mortality prior to maturity, accounted for 76 % of the variance in recruitment into mature adult populations. The low settlement rate coupled with the short life span of mussels Â« 3 years), meant that populations underwent marked spatial and temporal variations in structure and abundance as settlement intensity varied, but there were consistent general differences between mussel populations on dune rock and sandstone shores in Algoa Bay and on the open coast. It was concluded from these results that, spawning intensity and post-settlement growth and mortality, rather than dispersal, regulated recruitment and the structure and abundance of intertidal P. perna and C. meridionalis populations along the south coast of southern Africa. On the basis of these results it is recommended that species with limited dispersal, variable recruitment and high natural mortality, such as P. perna, should be conserved by protecting a small part of the population in reserves, and controlling utilisation outside reserves to minimize disturbance to local brood stocks. Furthermore, since the potential for reseeding adjacent exploited areas is limited, several small reserves placed at regular intervals along the coast would be more effective than a single large reserve.
Keywords: Perna -- South Africa -- Eastern Cape -- Algoa bay; Mytilus galloprovincialis -- South Africa -- Eastern Cape -- Algoa bay; Mytilidae -- South Africa -- Eastern Cape -- Algoa bay